Modified New Iterative Method for Solving Nonlinear Partial Differential Equations - Alaa K. Jabber (JOURNAL OF ADVANCES IN MATHEMATICS, 2020)
In this paper, the iterative method, proposed by Gejji and Jafari in 2006, has been modified for solving nonlinear initial value problems. The Laplace transform was used in this modification to eliminate the linear differential operator in the differential equation. The convergence of the solution was discussed according to the modification proposed. To illustrate this modification some examples were presented.